PENGARUH MINAT PADA LAGU BAHASA INGGRIS TERHADAP KEMAHIRAN MENDENGARKAN SISWA DI SMA KRISTEN IRENE MANADO - ANGMALISANG, HELEN YULIANA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
This skripsi is entitled ?Pengaruh Minat pada Lagu Bahasa Inggris terhadap Kemahiran Mendengarkan Siswa di SMA Kristen Irene Manado?. The objective of this research is to analyze in what extent the interest in English songs have an effect on students? listening skills in SMA Kristen Irene Manado. This research is based on the theory of Slameto (2010) stating that learning is more successful when dealing with interest of students. In conducting this study, the writer uses quantitative approach in order to investigate a particular population or sample with data collection using research instruments, and data analysis focusing on quantitative/statistical analysis to test the hypotheses that have been set. Questionnaire and test are used as the research instruments. The population of this research is the students in SMA Kristen Irene, and the sample is the twelve grader students as many as 31 students. The data is analyzed using regression-correlation analysis. The result of this research shows a significantly positive correlation between interest in English songs and listening skills. The effect of interest in English songs to listening skills is 71.1%. In conclusion, interest in listening to English songs makes people repeatedly do the activities that are related with English songs, with pleasant feelings which also add new knowledge. This knowledge helps listeners understand what they listen to. In addition, this interest also helps the listening process, since people?s attention is amplified when accompanied with personal interest, which help the listening process to be more effective. Keywords: interest, song, listening skills